2021
DOI: 10.1177/14799731211035822
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between prolonged physical and social isolation during the COVID-19 pandemic, reduced physical activity and disability in activities of daily living among people with advanced respiratory disease

Abstract: In people with advanced respiratory disease, we examined (i) the impact of COVID-19–related physical and social isolation on physical activity and (ii) relationships between time spent in isolation and disability in activities of daily living. Cross-sectional analysis was conducted in adults with advanced non-small cell lung cancer, chronic obstructive lung disease or interstitial lung disease. Measures included change in physical activity since physically and socially isolating (Likert scale) and disability (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
15
0
3
Order By: Relevance
“…Many have been concerned however, about a potential adverse consequence on physical activity (PA) and conditioning and on and mental and physical well being. In the journal this month Fettes et al 5 highlight this by measuring PA, self-reported disability and limits to performance of activities of daily living in people with advanced lung disease. PA in many patients was lower and was associated with self reported disability with a knock on effect on independence.…”
Section: The Downside Of Shielding During Lockdownmentioning
confidence: 99%
“…Many have been concerned however, about a potential adverse consequence on physical activity (PA) and conditioning and on and mental and physical well being. In the journal this month Fettes et al 5 highlight this by measuring PA, self-reported disability and limits to performance of activities of daily living in people with advanced lung disease. PA in many patients was lower and was associated with self reported disability with a knock on effect on independence.…”
Section: The Downside Of Shielding During Lockdownmentioning
confidence: 99%
“…Importantly, only 10% and 5% of participants received physiotherapy or occupational therapy interventions, respectively, within the month prior to the survey. 11…”
mentioning
confidence: 99%
“…The authors concluded that health and social care services will need to consider rehabilitation of those deemed clinically vulnerable as well as of those recovering from COVID-19. 11 The authors identified several risk factors to help identify the need for rehabilitation of individuals with chronic respiratory disease including (1) length of time spent in physical and social isolation, (2) presenting difficulty with and not only disability in daily activities, (3) symptom severity and (4) level of social support. They also proposed some strategies to prevent a further decline in disability in this population in case of a future pandemic: (1) minimize time spent in isolation, (2) maintain physical activity, (3) continue rehabilitation services or/and offer online alternatives, and (5) increase social support.…”
mentioning
confidence: 99%
See 2 more Smart Citations